Development of molecular markers for the Eucalyptus species identification - Rivera-Jimenez, Hernando J. [UNESP]; Rossini, Bruno C. [UNESP]; Leite, Vanusa do S. [UNESP]; Da Silva, Paulo H. M.; Marino, Celso L. [UNESP] (Univ Cordoba, Fac Ciencias Agricolas, 2017)
One of the main problems faced in several eucalypt breeding programs is the difficulty to identify the species and hybrids. This study aimed to find molecular markers associated with five species of Eucalyptus (E. saligna, E. tereticornis, E. urophylla, E. grandis and E. brassiana), by AFLP (Amplified Fragment Length Polymorphism) markers and BSA (Bulk Segregant Analysis), for their use in breeding programs in Brazil. In 33 primer combinations, a total of 868 polymorphic fragments was obtained, which represent a 91.65% of polymorphism. The best combinations that show potential markers for species identification were the primers M + GGT / E + ACC, which was linked to 70% of E. urophylla individuals. However, primer combination composed of M+GGA/E+ ACC identified 60% of individuals in the E. saligna species; combination by the primers M+GTC/E+AAC, confirmed two marks, one in 60% and the other in 50% of E. grandis individuals in the identification test. The treatment composed by the primers M+GGC/E+AAA, was confirmed in only 30% of E. brassiana individuals, being the same for the combination M+GGC/E+ACC primers, identifying 30% of E. tereticornis individuals. The AFLP analysis and BSA provide a quick tool for the identification of cultivars in Eucalyptus and can also be used to assist forest breeding programs.
Keywords: AFLP; BSA; Eucalyptus; species identification